The Influence of Current Ratio (Cr) and Return on Assets (Roa) on Net Profit at PT Sumber Alfariya Trijaya Tbk (Case study listed on the IDX for the period 2015-2022) - Fauzi, Azriel Muhammad Fauzi (PT FORMOSA CENDEKIA GLOBAL, 2024)
There is an assumption that a company's net profit is influenced by the Current Ratio and Return on Assets. The researcher found a relationship between the Current Ratio and Return on Assets and net profit. This quantitative research uses an associative descriptive approach, and PT. Sumber Alfariya Trijaya Tbk is the subject. The type of secondary data taken is the company's financial statements for 8 years, from 2015 to 2022. Documentation and literature study are two methods used to collect data. The financial statements of PT. The data were tested with classical assumptions, which include autocorrelation, normality, multicollinearity, and heteroscedasticity. Then correlation analysis, coefficient of determination, multiple linear regression analysis, and simultaneous partial t and f tests were carried out. The results of the t hypothesis test show that the current Current Ratio variable does not affect net profit; the significance value of 0.109 is greater than 0.05 and the calculated t value is greater than t table, which is -1.655 less than 1.699. The Return on Assets variable also affects net profit, with a significance value of 0.000 less than 0.05 and a calculated t value greater than t table, which is 32.771 greater than 1.699. The results of the f test of the Current Ratio and Return on Assets variables simultaneously affect net profit with a sig value of 0.000 less than 0.05 and a calculated f value > ft table, which is 537.533 greater than 2.934